Мультипликативные модели случайных процессов в многокомпонентных электронных системах - Тихонов, В. А.; Кудрявцева, Н. В. (ХНУРЭ, 2009)
In the presentation we introduce new classes of multiplicative models of linear prediction of Gaussian and non-Gaussian processes. We also describe the main principals of synthesis of the multiplicative models of the linear prediction. Furthermore, we give examples of multiplicative AR(p1)AR(p2) models construction.
Keywords: многокомпонентная электронная система; мультипликативная модель